Analysis of the Main Changes in Assessment and Approval of Medicines for Human Use in the Eurasian Economic Union - О. G. Nefidova; D. V. Babaskin; A. D. Sazonov; A. A. Kamaletdinova (Регуляторные исследования и экспертиза лекарственных средств)
The article presents a comprehensive analysis of the main changes to the Rules of marketing authorisation and assessment of medicinal products for human use in the Eurasian Economic Union (EAEU). The reflection of regulatory procedures in the legislation is quite a significant systemic feature that makes it possible to establish common requirements for the medicines present in the EAEU and to ensure the possibility of unified regulation of the matter within the national economies of the member states.